A delphi procedure on rehabilitation outcome for patients with moderate to severe traumatic brain injury; first phase of the Neurotraumatology Quality Registry (NET-QURE) - Lianne D. Peppel; Majanka H. Heijenbrok-Kal; Thomas A. van Essen; Godard C. W. de Ruiter; Wilco C. Peul; Gerard M. Ribbers (Medical Journals Sweden, 2022)
Objective: To select a set of rehabilitation outcome instruments for a national Neurotrauma Quality Registry (Net-QuRe) among professionals involved in the care of patients with traumatic brain injury. Design: A 3-round online Delphi procedure. Subjects: Eighty professionals from multiple disciplines working in 1 of the 8 participating rehabilitation centres were invited to participate. The response rate varied from 70% to 76% per round. Methods: For the Delphi procedure, multiple outcome categories were defined based on the International Classification of Functioning, Disability and Health (ICF) with concomitant measurement instruments. For each category we strived for consensus on one instrument of at least 75%. Results: After the first round, consensus was reached for the category subjective cognitive functioning. After the second round for quality of life, pain, general functioning, anxiety and depression, general psychological functioning, communication (impairment), and personal factors. Finally, after the third round, consensus was reached for activities of daily living, participation, self-awareness, and aphasia. No consensus was reached for the categories motor function, cognitive function, comorbidity, fatigue, and employment status. Conclusion: Consensus was reached in 12 out of 17 outcome categories. A Delphi procedure seems to be a feasible method to collectively select measurement instruments for a multicentre study.